The metabolism distribution and effect of dinotefuran in Chinese lizards (Eremias argus). (November 2018) - Wang, Yinghuan; Han, Yongtao; Xie, Yun; Xu, Peng; Li, Wei
Abstract: The Chinese lizards ( Eremias argus ) were used to evaluate the metabolism, distribution and effect of dinotefuran following oral exposed. The HPLC equipped with Q Exactive focus was used for metabolite identification and concentration analysis. After single oral administration, the time-concentration curves of dinotefuran and its metabolites were tissue-dependent. The liver and kidney were the major metabolic organs. Percutaneous and urinary excretions were the main ways for lizards to eliminate dinotefuran, and the urine output was the limiting factor. Nitro-reduction was an important process of the metabolism of dinotefuran that was dominated by aldehyde oxidase, and P450 enzymes were involved. The CYP3A4 and CYP2C19 played a crucial role in the other metabolic pathways of dinotefuran. The mRNA expressions of GST family were severely inhibited in liver, which showed dinotefuran might pose a risk of damaging the oxidative stress system in liver. Prolonged residuals of dinotefuran and its demethylation metabolite might enhance the risk of dinotefuran to brain. The results enrich and supplement the knowledge of the environmental fate of dinotefuran in reptiles. Graphical abstract: Image 1 Highlights: Molting and transurethral exclusion are the main routes for the elimination of DIN and its metabolites. AOX plays a major role in the nitro-reduction process of DIN. CYP3A4 and CYP2C19 play a crucial role in the metabolism of DIN. DIN may pose a risk of damaging the oxidative stress system in liver.